Impact of silver nanoparticles on secondary metabolite composition and toxicity in anise (Pimpinella anisum L.) callus culture - Ulusoy, Esma; Bozkurt, Aysenur; Durmaz, Sumeyye; Servi, Huseyin; Vardar, Filiz; Erisen, Semiha (BMC, 2024)
Background There are numerous challenges associated with producing desired amounts of secondary metabolites (SMs), which are mostly unique and cannot be chemically synthesized. Many studies indicate that nanoparticles (NPs) can boost the production of SMs. Still, the precise manner in which NPs induce metabolic changes remains unidentified. This study examines the influence of eco-friendly silver NPs (AgNPs) on the chemical makeup and toxicity of Pimpinella anisum L. (anise). Results AgNPs were introduced into anise callus cultures at different concentrations (0, 1.0, 5.0, 10, and 20 mg/L). The induced oxidative stress was tracked over intervals of 7, 14, 28, and 35 days. Chemical composition evaluations were carried out on the 35th day. Within the first 14 days, plant stress was evident, though the plant adapted to the stress later on. Notably, the plant showed high tolerance at 1 mg/L and 5 mg/L concentrations despite increased toxicity levels. However, relatively high toxicity levels were identified at 10 and 20 mg/L. The AgNP-induced stress significantly impacted anise SMs, particularly affecting fatty acid content. In the 10 and 20 mg/L AgNP groups, essential metabolites, including palmitic and linoleic acid, showed a significant increase. Polyunsaturated (omega) and monounsaturated fatty acids, vital for the food and pharmaceutical industries, saw substantial growth in the 1 and 5 mg/L AgNP groups. For the first time, vanillyl alcohol and 4-Hydroxybenzoic acid were detected along with various phenolic compounds, such as t-anethole, Salicylic acid, and Thiamazole. Conclusion AgNPs can function as an elicitor to efficiently generate essential SMs such as omegas and phenolic compounds in anise callus culture. This study explores the application of AgNPs as plant elicitors in anise SM production, offering invaluable insight into potential uses.
Keywords: AgNP; Secondary metabolites; Anise; Toxicity; Pimpinella anisum; Fatty acids; THALIANA GENE-EXPRESSION; SUPEROXIDE-DISMUTASE; ANTIOXIDANT ACTIVITY; CELL-CULTURES; FATTY-ACIDS; EXPOSURE; PLANTS; GROWTH; PHYTOTOXICITY; ELICITATION; Plant Sciences